The reasoning pattern of Islamic jurists' views on al-Rahn (Islamic Pawn Broking) contract and its ruling / Dziauddin Sharif , Amir Shaharuddin and Nurul Aini Muhamed - Sharif, Dziauddin; Shaharuddin, Amir; Muhamed, Nurul Aini (Academy of Contemporary Islamic Studies, 2016)
According to the Islamic jurisprudence, al-rahn is pledging a non-fungible property as surety against debt whereby the debt shall be paid from the pledged item in case of default. However, Muslim jurists differed in determining the nature of al-rahnu contract. The Hanafi, Shafi`i and Hanbali jurists viewed al-rahn as a charitable contract while the Maliki jurists considered it as a form of an exchange contract. These differences originated from their different interpretation of the verse 2: 283 in the Qur'an. Using the taxonomical classification approach by Rosch (1976), this paper examines the pattern of reasoning adopted by the jurists of the main schools of Islamic jurisprudence. Rosch's model is chosen as it can assist the researcher to categorize the aspects of discussion between the al-rahn nature, conditions and rulings. While the model consists of superordinate and subordinate relationships, the paper enhances the conceptual framework of al-rahn into the discussion of conditions and rulings. Thus, the harmonized effort of taxonomical classification is developed to discuss the related rulings resulted from the position of al-rahn as a form of charity or exchange contract. The study shows that Maliki and Shafi`i are seen to be the most consistent schools in holding their stance about al-rahn nature. The consistency can be identified through the examination of al-rahn rulings that matched with their original position. It is also found that the rulings of Maliki jurists are more lenient in stipulating conditions in the contract while Shafi`i stood otherwise.